QUBIC II: Spectral polarimetry with bolometric interferometry. Issue 4 (1st April 2022) - ,; Mousset, L.; Gamboa Lerena, M.M.; Battistelli, E.S.; de Bernardis, P.; Chanial, P.; D'Alessandro, G.; Dashyan, G.; De Petris, M.; Grandsire, L.; Hamilton, J.-Ch.; Incardona, F.; et al.
Abstract: Bolometric interferometry is a novel technique that has the ability to perform spectral imaging. A bolometric interferometer observes the sky in a wide frequency band and can reconstruct sky maps in several sub-bands within the physical band in post-processing of the data. This provides a powerful spectral method to discriminate between the cosmic microwave background (CMB) and astrophysical foregrounds. In this paper, the methodology is illustrated with examples based on the Q & U Bolometric Interferometer for Cosmology (QUBIC) which is a ground-based instrument designed to measure the B-mode polarization of the sky at millimeter wavelengths. We consider the specific cases of point source reconstruction and Galactic dust mapping and we characterize the point spread function as a function of frequency. We study the noise properties of spectral imaging, especially the correlations between sub-bands, using end-to-end simulations together with a fast noise simulator. We conclude showing that spectral imaging performance are nearly optimal up to five sub-bands in the case of QUBIC.